Physical and physiological characterization of heteromorphic seeds of Erythrina velutina Willd. - Hannah Lanier de Oliveira; Clarisse Pereira Benedito; Giovanna Dias de Sousa; Pablo Ferreira da Silva; Salvador Barros Torres; Daise Feitoza da Rocha (Journal of Seed Science)
ABSTRACT: Erythrina velutina Willd. is a xerophytic plant native to the Caatinga, whose seeds show heteromorphism in seed coat color, varying between reddish and orangish. This study aims to analyze the influence of seed coat color on the physical characteristics, dormancy and physiological potential of the seeds of this species. The seeds were evaluated for length, width, moisture content, hundred-seed weight, water absorption curve, first count, germination, hard seeds, shoot and root length, and shoot and root dry mass. In addition, cross-sectional fragments of 10 seeds of each color were examined by means of a scanning electron microscope (SEM), which was used to visualize the epidermis, palisade layer and parenchyma cell layers. The experimental design was completely randomized with four replications of 25 seeds in a 2 x 2 factorial scheme, considering seed coat color (orangish and reddish) and dormancy overcoming (intact and scarified seeds). The data were subjected to analysis of variance and compared by Tukey test at 5% probability level. There was no significant influence of seed coat color on the physical characterization of the seeds. It was found that reddish seeds have greater dormancy and lower physiological potential when compared to orangish seeds.